How social and economic policies have affected the genome of mezcal agaves: The contrasting stories of Bacanora and Espadín - Anastasia Klimova; Jesús N. Gutiérrez Rivera; Erika Aguirre-Planter; Luis E. Eguiarte (PLoS ONE, 2025)
Plant domestication in Mesoamerica gave the world crops of global significance, such as maize, beans, squashes, cocoa, and cotton. Additionally, it has introduced species of regional economic importance, which still display intermediate levels of domestication, including Agave, Opuntia, columnar cacti, Amaranthus, and various ornamental species. Agaves, in particular, hold immense cultural and economic significance in Mexico and play a crucial ecological role in wild plant communities. However, current agricultural practices have negatively impacted both wild populations of agave through overexploitation and habitat destruction, as well as cultivated plants by reducing available landraces and promoting the use of homogeneous plant material. Using genomic data (RADseq) and over 50,000 SNPs, we aimed to assess how local social and political decisions may have influenced genomic diversity and differentiation in intensively managed, clonally propagated Agave angustifolia (Espadín) in the state of Oaxaca, the cultivated A. angustifolia used to produce mezcal known as Bacanora in the state of Sonora, and their wild counterparts from both regions. We found evidence suggesting that Espadín recently arose through farmer selection of a clonal lineage with desirable mezcal production attributes (i.e., hybrid vigor), apparently from an unsampled cultivated variety, a cross between genetically distinct wild populations, or by hybridization between wild and cultivated plants. Espadín samples were represented by closely related heterozygous genotypes, with considerable genetic differentiation from wild plants. On the other hand, the genomic composition of cultivated Bacanora agave appears to have been influenced by a recently lifted ban (in 1992) on its cultivation and distillation, which, along with the relatively lower popularity of this beverage, allowed cultivated Bacanora agave to maintain the genetic diversity found in wild populations of the region. We found that social and political decisions may have important impacts on crop genomic diversity and differentiation.